The implementation of adaptive algorithms to optimize the dynamic system - Nazarov, А.; Gavva, О.; Назаров, А. С.; Гавва, О. С.; Назаров, О. С. (Харківський національний автомобільно-дорожній університет, 2015)
The implementation of adaptive algorithms to optimize the dynamic system by constructing an adaptive control system chassis DCC is consider in the article.
Реализация адаптивных алгоритмов для оптимизации динамической системы
Реалізація адаптивних алгоритмів для оптимізації динамічної системи
Keywords: adaptive control algorithm; control system chassis; vehicle and road environment; алгоритм адаптивного управления; система управления ходовой части; транспортное средство и среда дороги; алгоритм адаптивного управління; система управління ходової частини; транспортний засіб і середовище дороги; 629.195